(3CQLhRI GdLeGd Yf MGd GdQLGds - (3CMeO Hf eMeO GdYWGQ Hf Ydj GdMSjfj GdHZOGOj,J (B1215 (3g` s ((3eMeO Hf WGgQ GdSeGhj s)
(3ChdgG (B:s
(3CMeO ef CjOOjf CMeOG HBdg hef Hge bO EbJOi hgPg CQLhRI eNJUQI Yf Ld CMhGd GdQLGd eNHQg s
(3BNQgG (B:s
(3hGced GdUdGI hGdSdGe Ydi GdfHi GdeKHJ GdESdGe ef NJe Gddg Hg GdQSGdI hBdg GdZQ Phi GdLdGdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B232s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B23 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(399) s
Keywords: (3GdJGQjNs